If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9 + 6g = -4 + 7g Solving -9 + 6g = -4 + 7g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-7g' to each side of the equation. -9 + 6g + -7g = -4 + 7g + -7g Combine like terms: 6g + -7g = -1g -9 + -1g = -4 + 7g + -7g Combine like terms: 7g + -7g = 0 -9 + -1g = -4 + 0 -9 + -1g = -4 Add '9' to each side of the equation. -9 + 9 + -1g = -4 + 9 Combine like terms: -9 + 9 = 0 0 + -1g = -4 + 9 -1g = -4 + 9 Combine like terms: -4 + 9 = 5 -1g = 5 Divide each side by '-1'. g = -5 Simplifying g = -5
| 105*12=16a | | 5y=13-4x | | 14-2a=4a | | 5y/6-2=1-2y/3 | | (x+10)*2=2y-62 | | 9z=-6+6z | | 5x^5+2= | | x+6(-2.2)=27 | | -7b=-5b-8b | | 6m=5m+9 | | (4a^2-9)=0 | | -6c=-5c-7 | | 17+5-7=10+2x+3x | | 3j-7=10j | | 36y^2=30y | | -7d=-6d-7 | | 3(15+6y)+2y=1 | | 14sinx=0.236127203 | | 5x+9=3+15 | | 5y+3y-6y-y=11 | | 1/3x-5/4=-4/5 | | X+6x-9=7x+3x | | 3(x-2)=95 | | 4w-3(-4z+4w)-3z= | | x^2+5-5=0 | | 8b+2b+5b+5b=20 | | 4.6n=43.24 | | 10x+70=7x+100 | | X-6x-9=7x+3x | | -9n+8=(-8n)-7 | | 8t-2t+3t-9t+4t=12 | | 15v+2v-16v=20 |